Spatial and non-verbal reasoning abilities in first-year female DVM students before and after 4 h of canine osteology training or 19 h of canine dissection: preliminary study - Gutierrez, J. Claudio; Nlebedum, Uchenna; Wanakumjorn, Patrawin; Holladay, Steven D. (Frontiers in Veterinary Science, 2025)
Spatial ability refers to human cognitive ability to form, retrieve, and mentally manipulate models of spatial nature. This critical component of human intellect is relevant on a wide spectrum of professional disciplines including engineering, architecture, mathematics, computer sciences, natural sciences and a variety of medical disciplines, including anatomy and diagnostic imaging. In the present study, validated testing tools were used to compare spatial and general non-verbal reasoning abilities in first-year female veterinary medical students. These tests were: Guay’s Visualization of Views Test (GVVT) and, Raven’s Advanced Progressive Matrices Test, short form (APMT). Osteology Group (OG): students took the tests before and after exposure to general canine osteology (4 h). Dissection Group (DG): students took the tests before and after exposure to dissections/pro-sections/palpation labs (19 h). Results for the OG showed a numeric but non-significant increase in GVVT (p = 0.092), with mean scores of 8.01 and 11.34 pre-training and post-training, respectively. Similar results were found for the APMT, with pre-training and post-training mean scores of 7.44 and 8.44 (p = 0.16), respectively. Results for the DG showed a numeric but non-significant increase in GVVT (p = 0.67), with mean scores of 11.77 and 13.28 pre-labs and post-labs, respectively. For the APMT, the increase in scores was significant (p = 0.028), with mean scores of 6.8 and 10.2, pre-labs and post-labs, respectively. Future studies are planned with greater numbers of students and groups with different hours of anatomy exposure. Future studies might also consider subgroups such as pre-veterinary students.